2015
DOI: 10.1111/cen.12986
|View full text |Cite
|
Sign up to set email alerts
|

Influence of race/ethnicity on cardiovascular risk factors in polycystic ovary syndrome, the Dallas Heart Study

Abstract: Objective Polycystic ovarian syndrome (PCOS) is estimated to affect up to 20% of women. PCOS is associated with insulin resistance and cardiovascular (CV) risk factors. We aimed to evaluate the impact of race/ethnicity on the prevalence of CV risk factors and subclinical predictors of CV events. Design Cross-sectional analysis of data collected by the Dallas Heart Study, an urban, population-based cohort oversampled for blacks. Patients A previously described cohort of women with PCOS and control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 43 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…In contrast, some studies found comparable 24-hour ambulatory BP levels between PCOS and control groups, but that finding might be due to small study populations (8)(9)(10). Of note, our study population included only women of Caucasian ethnicity and may therefore differ from other populations regarding the prevalence of hypertension and other cardiovascular risk factors, as race/ethnicity has also been reported to affect these risks in women with PCOS (26). Our results are therefore best generalized to Caucasian populations.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, some studies found comparable 24-hour ambulatory BP levels between PCOS and control groups, but that finding might be due to small study populations (8)(9)(10). Of note, our study population included only women of Caucasian ethnicity and may therefore differ from other populations regarding the prevalence of hypertension and other cardiovascular risk factors, as race/ethnicity has also been reported to affect these risks in women with PCOS (26). Our results are therefore best generalized to Caucasian populations.…”
Section: Discussionmentioning
confidence: 72%
“…While PCOS is strongly associated with many traditional cardiovascular disease risk factors (3), it has remained unclear if PCOS is an independent risk factor for hypertension. An Australian study including 26 women with self-reported PCOS and hypertension (mean age: 28-33 years) reported that in normal-weight group, self-reported hypertension was more prevalent in PCOS than control group, whereas in the overweight/obese group the prevalence of hypertension was similar, and in the multivariate regression analysis PCOS was not significantly associated with hypertension (6). Furthermore, a hospital-based study population of 35 women with PCOS who had underwent wedge resection reported that these women had significantly higher prevalence of hypertension based on hospital discharge register information, even though clinically measured blood pressure (BP) levels were similar between PCOS and control groups (7).…”
Section: Introductionmentioning
confidence: 99%
“…Search results Figure 1 presents the search strategy and study selection. Of 5236 records retrieved through searching databases 30 studies including 17 population based [2,3,7,19,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 11 non-population based studies [4,5,10,34,[49][50][51][52][53][54][55][56] were selected for the final analyses. Twenty-four studies assessed a population of reproductive age patients with PCOS [2, 3, 5, 7, 10, 34-38, 40, 41, 43-47, 49-51, 53-56], 4 studies-menopausal/aging women [19,39,52,57], and two studies-both age groups of patients (reproductive and menopausal/aging women) [4,48].…”
Section: Resultsmentioning
confidence: 99%
“…dyslipidemia, metabolic syndrome, C-reactive protein are elevated in patients with PCOS [2][3][4][5][6]; these risk factors are present even in young PCOS patients and predispose to development of early atherosclerosis, cardiovascular morbidity and mortality [5,7,8].…”
mentioning
confidence: 99%
“…In the present study, no significant relation was detected between BMI and plasma viscosity for women with PCOS, although this may be due to the narrow range of BMI values of the present women. Moreover, differences in the ethnicities of the present women and those of the previous study [14] may explain discordant findings, as ethnicity of women with PCOS has been demonstrated to influence the profile of cardiovascular risk factors [26]. Elevated plasma viscosity in PCOS is likely the result of increased plasma fibrinogen concentration, given the viscosity of plasma is determined by its protein content, and fibrinogen’s relatively large molecular weight and fibrous structure make it the most important plasma protein in this regard [27].…”
Section: Discussionmentioning
confidence: 89%